Peran Komunitas Belajar Untuk Meningkatkan Mutu Pembelajaran Di SMP Muhammadiyah Yogyakarta - Cholivah, Wahyu; Hidayati, Dian; Sukirman (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Learning quality is the level of success and effectiveness of a learning process in achieving predetermined educational goals, but in reality the quality of learning in Indonesia is still relatively low. So this research aims to analyze the role of learning communities in improving the quality of learning. The method used in this research is a qualitative research method. The data collection and analysis techniques are observation, interviews and documentation. The results of this research show that the learning community plays a role in improving the quality of learning. This can be seen from the role it plays in carrying out the adaptation process, achieving goals, integrating and maintaining patterns so that the continuity of guidance provided by the learning community has a big impact on the quality of learning. The following important roles of learning communities in education and individual development include Teacher Professional Development, Collaboration Among Teachers, and Learning Innovation.